Hydrogeochemical Characteristics and The Impact of Anthropogenic Activity on Groundwater Quality in the Banjaran Sub Urban Area West Java Indonesia. - Rizka Maria; Teuku Yan Waliana Muda Iskandarsyah; Bombom Rachmat Suganda; Hendarmawan Hendarmawan (Institut Teknologi Bandung, 2022)
Abstract Banjaran Sub Urban Area in the Southern of Bandung Basin is a volcanic area with variations in lithology and anthropogenic activity that is growing. This study aims to determine the effect of geology and the environment on groundwater hydrochemical conditions in volcanic regions. The method that used are piper diagrams, Gibbs diagrams, correlation and major ion bivariate. Retrieval of 23 groundwater samples consisting of 10 dug wells, 10 drilling wells and 3 springs. The results showed that the groundwater interaction process was influenced by rock weathering. The hydrogeochemical process of major ions in groundwater volcanic regions is characterized by weathering of silica. Groundwater facies are CaMgCl, CaMgHCO3, NaHCO3. The hydrogeochemical process of major ions in groundwater volcanic regions is characterized by weathering of silica. Groundwater upstream area dominated influence by the groundwater-rock interaction, while groundwater downstream area was influenced by anthropogenic factors. Shallow groundwater with land cover agricultural and settlements is more susceptible to contamination by anthropogenic activities. High structural control allows water to flow through the fracture and facilitates the groundwater dilution process, thus helping the process of rock-water interaction. Keywords: Anthropogenic, hydrogeochemical, water-rock interaction, rock weathering. Abstrak. Banjaran adalah wilayah sub urban di daerah vulkanik Cekungan Bandung Selatan yang mengalami perkembangan antropogenik secara dinamis. Disisi lain, variasi kondisi geologi di daerah penelitian berpengaruh pada interaksi batuan dan airtanah. Berdasarkan pada latar belakang tersebut, penelitian ini bertujuan untuk mengetahui pengaruh geologi dan lingkungan terhadap kondisi hidrokimia airtanah di daerah vulkanik. Metode yang digunakan adalah diagram piper, diagram Gibbs, korelasi dan bivariat ion utama. Pengambilan sampel airtanah sebanyak 23 sampel yang terdiri dari 10 sumur gali, 10 sumur bor dan 3 mata air. Hasil penelitian menunjukkan bahwa proses interaksi airtanah dipengaruhi oleh pelapukan batuan. Proses hidrogeokimia ion-ion utama di daerah vulkanik air tanah dicirikan oleh pelapukan silika. Fasies airtanah adalah CaMgCl, CaMgHCO3, NaHCO3. Proses hidrogeokimia ion-ion utama di daerah vulkanik air tanah dicirikan oleh pelapukan silika. Daerah hulu airtanah dipengaruhi oleh interaksi airtanah-batuan, sedangkan daerah hilir airtanah dipengaruhi oleh faktor antropogenik. Airtanah dangkal dengan tutupan lahan pertanian dan pemukiman lebih rentan terhadap pencemaran oleh aktivitas antropogenik. Kontrol struktural yang tinggi memungkinkan air mengalir melalui rekahan dan memudahkan proses pengenceran air tanah, sehingga membantu proses interaksi airtanah-batuan. Kata kunci: Antropogenik, hidrogeokimia, interaksi airtanah-batuan, pelapukan batuan.